ВІДРОДЖЕННЯ КОЗАЦТВА НА ПІВДЕННОМУ ЗАХОДІ УКРАЇНИ (1917-1918 рр). (Zaporizhzhia Historical Review, 2021)
The author of the article attempts to trace the process of organization and activities of the Free Cossacks in the South-West of Ukraine. The social background and the peculiarities of Free Cossacks development in the South-West region are elucidated. The character of the movement and the attitude of different political forces to it are also under consideration in this paper. The special attention is given to the participation of Free Cossacks in the First Ukrainian Bolshevist war and its subsequent fortunes after its liquidation in April-May 1918.